Comparison of intratumor and local immune response between MV X-ray FLASH and conventional radiotherapies - Hongyu Zhu; Dehuan Xie; Ying Wang; Runda Huang; Xi Chen; Yiwei Yang; Bin Wang; Yinglin Peng; Jianxin Wang; Dexin Xiao; Dai Wu; Chao-Nan Qian; et al. (Clinical and Translational Radiation Oncology, 2023)
Background/Purpose: Investigating the antitumor effect and intratumor as well as local immune response in breast cancer-bearing mice after MV X-ray ultra-high dose rate radiotherapy (FLASH-RT) and conventional dose rate radiotherapy (CONV-RT). Materials/Methods: Six-week-old female C57BL/6 mice were inoculated subcutaneously with Py8119 and Py230 breast tumor cells in the inguinal mammary gland and administered 10 Gy abdominal 6 MV X-ray FLASH-RT (125 Gy/s) or CONV-RT (0.2 Gy/s) 15 days after tumor inoculation. Tumor and spleen tissues were obtained at different time points post-irradiation (PI) for analysis of immune cell infiltration using flow cytometry and immunohistochemical (IHC) staining. Intestine tissues were collected 3 days PI to evaluate normal tissue damage and immune cell infiltration. Results: Both FLASH-RT and CONV-RT significantly delayed tumor growth. Flow cytometry showed increased CD8+/CD3 + and CD8+/CD4 + ratios, and IHC confirmed a similar increased CD8 + T cell infiltration at 2 weeks PI in Py8119 tumor tissues in both irradiation groups. No statistical difference was observed between the irradiation groups in terms of tumor growth and increased T cell infiltration in the tumor. Unexpectedly, significantly smaller spleen weight and substantially higher CD8+/CD3 + and lower CD4+/CD3 + ratios were observed in the spleens of the FLASH-RT group than in the spleens of the non-irradiated control and CONV-RT groups 4 weeks PI. Pathological analysis revealed severe red pulp expansion in several spleens from the CONV-RT group, but not in the spleens of the FLASH-RT group. Reduced intestinal damage, macrophage and neutrophil infiltration were observed in the FLASH-RT group compared with CONV-RT group. Conclusions: FLASH-RT and CONV-RT effectively suppressed tumor growth and promoted CD8 + T cell influx into tumors. FLASH-RT can induce different splenic immune responses and reduce radiation-induced damage in the spleen and intestine, which may potentially enhance the therapeutic ratio of FLASH-RT.